2015
DOI: 10.1007/s10118-014-1475-0
|View full text |Cite
|
Sign up to set email alerts
|

Influences of hyperbranched polyethylenimine on the reactive compatibilization of polycarbonate/polyamide blends

Abstract: The influences of hyperbranched polyethylenimine (hPEI), which possesses many reactive amino end-groups, on the blending properties of bisphenol-A polycarbonate (PC) and amorphous polyamide (aPA) were systematically investigated. Scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) were used to observe the effect of hPEI on morphologies of PC and aPA phases in bulk blends. While the interfacial fracture toughness between planar PC and aPA layers with and without hPEI was studied by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Inspired by previous studies regarding ethylene­diamine aminolysis of PET and in efforts to expand the scope of reactive compatibilization for PET/HDPE blends, we envisioned that amino-telechelic polyethylene (ATPE) could react with the ester linkages of PET, affording a PET–PE multiblock poly­(ester amide) that would ultimately serve as a blend compatibilizer (Scheme ). Compatibilization via aminolysis is advantageous in that the reaction proceeds without catalysis and has been previously demonstrated in PET/polyamide and polycarbonate/polyamide blends. Furthermore, ATPE can cocrystallize with the HDPE phase, potentially leading to enhanced compatibilization compared to amorphous compatibilizers such as PEGMA and PEGMMA.…”
Section: Introductionmentioning
confidence: 92%
“…Inspired by previous studies regarding ethylene­diamine aminolysis of PET and in efforts to expand the scope of reactive compatibilization for PET/HDPE blends, we envisioned that amino-telechelic polyethylene (ATPE) could react with the ester linkages of PET, affording a PET–PE multiblock poly­(ester amide) that would ultimately serve as a blend compatibilizer (Scheme ). Compatibilization via aminolysis is advantageous in that the reaction proceeds without catalysis and has been previously demonstrated in PET/polyamide and polycarbonate/polyamide blends. Furthermore, ATPE can cocrystallize with the HDPE phase, potentially leading to enhanced compatibilization compared to amorphous compatibilizers such as PEGMA and PEGMMA.…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, very less attention was placed upon self-healing on rubber using polyethylenimine (PEI), which is neither extrinsic nor intrinsic type healing mechanism. 3 Wang et al 4 investigated the influence of hyperbranched PEI (hPEI) with M w of 10,000 g/ mol on the blending properties of bisphenol-A polycarbonate (PC) and amorphous polyamide (aPA) which were substantially immiscible. They found that the compatibility of the PC/aPA blend could be significantly improved by incorporating hPEI.…”
Section: Introductionmentioning
confidence: 99%
“…A great quantity of research has indicated that the reactive-comb-like compatibilizers usually exhibit better compatibilizing effects due to the double-comb structures. The double-grafted side chains of the compatibilizers can stabilize the dynamic balance of the neighboring phases at the interface [13][14][15][16]. This technique is based on the in-situ formation of double-grafted copolymers at polymer-polymer interface, which substantially lowers interface tension, suppresses particle coalescence, and ultimately exhibits enhanced physical properties [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%